4‐Methyl morpholinium bis‐(thio)barbiturates: Synthesis, structure, anticancer evaluation, and CoMFA study. Issue 9 (2nd September 2020) - Noroozi Pesyan, Nader; Rashidnejad, Hamid; Esmaeili, Mohammad Ali; Safari, Elnaz; Tunç, Tuncay; Alilou, Mostafa; Safavi‐Sohi, Reihaneh; Şahin, Ertan
Abstract: The reaction of symmetrical (thio)barbituric acids with aldehydes in the presence of 4‐methyl morpholine yielded a new form of 4‐methyl morpholinium bis‐(thio)barbiturate containing charge‐separated intermolecular and eight‐membered intramolecular H ‐bonds. X‐ray Crystallography, FT‐IR, and 1 H and 13 C‐NMR spectroscopy techniques were used for structure characterizations. Some of these compounds showed potent anticancer activities. Cytotoxicity of the synthetic compounds against HeLa and MCF‐7 cell lines were performed by MTT assay. In addition, a comparative molecular field analysis was carried out, and the effects of substituents on the biological activities of these compounds were explained. Abstract : Reaction of symmetrical (thio)barbituric acids with aldehydes in the presence of 4‐methyl morpholine afforded a new form of 4‐methyl morpholinium bis‐(thio)barbiturate containing charge‐separated intermolecular and eight‐membered intramolecular H ‐bonds.